The Influence of Tax Understanding and Income Tax Incentives on MSME Tax Compliance, Moderated by Tax Digitalization - Putri, Helmalia; Din, Muhammad; Furqan, Andi Chairil; Tanra, Andi Ainil Mufidah (GoAcademica Research & Publishing, 2024)
This study investigates how tax knowledge and income tax incentives affect tax compliance among MSMEs, with tax digitalization functioning as a moderating variable. MSMEs are vital to Indonesia's economy, yet achieving tax compliance in this sector poses significant challenges, especially in Palu, which has been heavily impacted by the 2018 natural disaster and the COVID-19 pandemic. In response to these difficulties, the government launched several measures, including Regulation No. 44 of 2020, which offers tax incentives for businesses affected by the pandemic. However, as of May 2020, the adoption of these incentives among MSME operators was notably low (D. Setiawan, 2018). This situation led researchers to explore whether MSMEs in Palu have effectively taken advantage of these income tax incentives. The research utilized a quantitative methodology, employing a Likert scale to measure the impact of the independent variables on the dependent variable. The population for the study comprised MSMEs registered with the Department of Cooperatives, MSMEs, and Labor in Palu, with purposive sampling used to select respondents based on specific criteria. Data collection was conducted manually using questionnaires, and the analysis was performed using WarpPLS 7.0. The findings indicated that tax knowledge significantly and positively influences MSME tax compliance, and income tax incentives also demonstrate a substantial positive effect. Although tax digitalization does not significantly moderate the relationship between tax knowledge and compliance, it does play a moderating role in the effect of income tax incentives on compliance.